Cities & social change encounters with contemporary urbanism - Paddison, Ronan; McCann, Eugene (Los Angeles, California SAGE, 2014)
What is the city? What is the nature of living in the city? This text provides an in-depth understanding of the central issues associated with the city and how living in a city impacts its inhabitants. Theoretically informed and thematically rich, the book contains an eminent, international cast of contributors and contributions. It provides a critical analysis of the key thinkers, themes and paradigms dealing with the relationship between the built environment and urban life. It includes illustrative case studies, questions for discussion, further reading and web links. Examining the contradictions, conflicts and complexities of city living, this book is an essential resource for students looking to get to grip with the different theoretical and substantive approaches that make up the diverse and rich study of the city and urban life.
Encountering the city : multiple perspectives on urban social change Ronan Paddison and Eugene McCann -- Representing and imagining the city Regan Koch and Alan Latham -- The new middle class, lifestyle and the new gentrified city Loretta Lees -- Being poor in the city Geoff DeVerteuil -- Living with difference : reflections on geographies of encounter Gill Valentine -- The everyday city of the senses Mónica Degen -- Disorder and the regulation of urban space Steven Herbert and Tiffany Grobelski -- Walling the city Gordon MacLeod -- Health and the city Graham Moon and Robin Kearns -- Cities, nature and sustainability Ian Cook and Eric Swyngedouw -- Just cities James deFilippis and Juan Rivero -- The good city? Ananya Roy -- Engaging the urban world Eugene McCann and Ronan Paddison.
Includes bibliographical references (pages 226-261) and index.
Keywords: Cities and towns; Sociology, Urban; Social change